2019
DOI: 10.1177/1010428319860400
|View full text |Cite
|
Sign up to set email alerts
|

3′ untranslated region A>C (rs3212227) polymorphism of Interleukin 12B gene as a potential risk factor for Hodgkin’s lymphoma in Brazilian children and adolescents

Abstract: Interleukin 12 plays an important role in immunoregulation between the T helper 1/T helper 2 lymphocytes and in the antiviral and antitumor immune response. The aim of this study was to investigate the possible association between the interleukin 12B polymorphism rs3212227 and the risk to develop Hodgkin’s lymphoma in childhood and adolescents. A total of 100 patients with Hodgkin’s lymphoma and a group of 181 healthy controls were selected at random from a forensic laboratory of the University of Pernambuco. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…*p value ≤ 0.05 significant while **p value ≤ 0.01 highly significant should induce allergen non-responsiveness and prevent IgE isotype switching, whereas if present late in the allergic response, IgE secretion by B lymphocytes may be enhanced [41]. IL-12 has multiple biological activities, and it is a key factor that drives Th1 responses and IFN-γ production [42]. Our results demonstrated a significantly lower serum level of IL12B in patients with dust mites allergy as compared to controls as shown in several studies where IL-12 mRNA expression and IL12b levels were lower in atopic patients compared to controls [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…*p value ≤ 0.05 significant while **p value ≤ 0.01 highly significant should induce allergen non-responsiveness and prevent IgE isotype switching, whereas if present late in the allergic response, IgE secretion by B lymphocytes may be enhanced [41]. IL-12 has multiple biological activities, and it is a key factor that drives Th1 responses and IFN-γ production [42]. Our results demonstrated a significantly lower serum level of IL12B in patients with dust mites allergy as compared to controls as shown in several studies where IL-12 mRNA expression and IL12b levels were lower in atopic patients compared to controls [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies investigated the effect of the IL-12B rs3212227 polypeptide synthesis, thereby altering the cytokine's production (Silva et al, 2019). As for IL-12Rβ2 rs3790565(C/T) (located in the intron of IL-12Rβ2 gene at position chr1:67345673), several studies have suggested that this SNP may have immunoregulatory functions, resulting in a modification of inflammatory responses, especially those mediated by IL-12 (Hirschfield et al, 2009).…”
Section: Introductionmentioning
confidence: 99%